2020
DOI: 10.1177/0888325419897987
|View full text |Cite
|
Sign up to set email alerts
|

“Vrem o ţară ca afară!”: How Contention in Romania Redefines State-Building through a Pro-European Discourse

Abstract: This article belongs to a forthcoming special cluster, “Contention Politics and International Statebuilding in Southeast Europe” guest-edited by Nemanja Džuverovic, Julia Rone and Tom Junes. Massive protest waves, mainly led by younger citizens, appeared during the past years in Romania. [Gubernat and Rammelt] provide an analysis of the production of meaning by the “Romanian street” as a collective actor. They argue that “Vrem o ţară ca afară! (We want a country like abroad!)” became the leitmotif for importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As I show, through this visual discourse AUR promoted its platform and formulated counter-hegemonic narratives directed against democratic institutions and conventions during the health crisis. Theoretically, it is my hope that this article will contribute to the literature on anthropological theories of social change and the growing body of protest movements from EE and Romania (Abăseacă 2018;Gubernat and Rammelt 2021;Vesalon and Creţan 2015;Chiruta 2020;Adi and Lilleker 2017). I begin with a short overview of the literature on rituals of rebellions and ceremonial revolution, followed by an outline of a theory of hegemony and counter-hegemony.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As I show, through this visual discourse AUR promoted its platform and formulated counter-hegemonic narratives directed against democratic institutions and conventions during the health crisis. Theoretically, it is my hope that this article will contribute to the literature on anthropological theories of social change and the growing body of protest movements from EE and Romania (Abăseacă 2018;Gubernat and Rammelt 2021;Vesalon and Creţan 2015;Chiruta 2020;Adi and Lilleker 2017). I begin with a short overview of the literature on rituals of rebellions and ceremonial revolution, followed by an outline of a theory of hegemony and counter-hegemony.…”
Section: Introductionmentioning
confidence: 92%
“…The research has shown the utility of incorporating the concept of counter-hegemony in social media analyses of protests movements (Navumau 2019), newspaper content analyses of grassroots movements (De Cillia and McCurdy 2020) and the transnational discourses of far-right parties in Europe on ethnic issues (Balci and Cicioglu 2020). When investigating power contestation in Romania, several studies reveal a rich tradition of voices of discontent (Burean and Badescu 2014), anti-government mobilisation in times of crisis (Abăseacă 2018) and cases where Western hegemonic discourse has been utilised to frame national discontent (Gubernat and Rammelt 2021). To link this study with the above research, I interconnect Kubik's work on counter-hegemony with Laclau's theorisation of discourse.…”
Section: Rituals Ceremonial Revolution and Counter-hegemony In Discou...mentioning
confidence: 99%
“…The 2017 #rezist/OUG13 anti-corruption protests in Romania represent a case of sustained protests against an ongoing political issue endemic to post-communist political systems: the corruption of the political elites (Olteanu & Beyerle, 2017). Recent activism in Romania has been nationally-oriented, defined by an overarching concern with the effects of communism in the democratic and economic development of the country, and reflective of the pro-European, middle-class ethos (Gubernat & Rammelt, 2021). A cause of ongoing protest, corruption has been framed by local activists and political commentators as a consequence of communism's "unresolved issues of the past" (Abăseacă, 2018, p. 681), eventually growing into a "quasi-hegemonic metanarrative and identity marker of the urban middle class in Romania" (Kiss & Székely, 2021, p. 11).…”
Section: The 2017 Anti-corruption Protests In Romaniamentioning
confidence: 99%
“…The 2017 #rezist protests were fueled by ongoing discontent, largely among the urban young and the middle-class, with the corruption of the political elites represented by the ruling Social Democrat Party (PSD; Gubernat & Rammelt, 2021;Kiss & Székely, 2021). The party's president, Liviu Dragnea, had a previous fraud conviction and was under criminal investigation for another act of corruption at the time of the protests.…”
Section: The 2017 Anti-corruption Protests In Romaniamentioning
confidence: 99%
See 1 more Smart Citation